2008
DOI: 10.1148/radiol.2462062166
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of MR Image Lung Volume Measurement in Fetuses with Congenital Diaphragmatic Hernia and in Vitro Lung Models

Abstract: The reliability and validity of MR volume measurements are high. The method is independent of the sequence and the imaging plane and can be performed with a very good interobserver agreement, even in small volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 47 publications
1
66
0
4
Order By: Relevance
“…The reproducibility of the ADC measurement was then evaluated by using the intraclass correlation coeffi cient (ICC) for each of breath-hold and respiratorytriggered DW imaging pair ( 19,20 ). An ICC greater than 0.75 was considered to represent good agreement ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproducibility of the ADC measurement was then evaluated by using the intraclass correlation coeffi cient (ICC) for each of breath-hold and respiratorytriggered DW imaging pair ( 19,20 ). An ICC greater than 0.75 was considered to represent good agreement ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…An ICC greater than 0.75 was considered to represent good agreement ( 19 ). To estimate the magnitude of change in ADCs that can confi dently be detected in a single individual, the 95% limits of agreement between the ADCs measured …”
Section: Discussionmentioning
confidence: 99%
“…The mean difference in THC between the two reviewers was not statistically significant. In this study, we did not verify validity, which assesses whether a test is actually measuring what it is purporting to measure and therefore expresses the measurement accuracy [37], because we did not evaluate the actual measurements of microvessel density count with immunohistochemical staining such as antihuman von Willebrand factor. Zhu et al reported the correlation coefficient between histological microvessel density count and haemoglobin distribution as 0.64 (P<0.05) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Concernant les pathologies pulmonaires et diaphragmatiques, l'é tude de D Levine en 2003 [18] dé montrait pour l'IRM, un apport diagnostic proche de 40 %. Dans les hernies diaphragmatiques, cette imagerie est systé matiquement ré alisé e afin de pré ciser les é lé ments pronostics du contenu hernié comme la pré sence de foie et pré ciser le volume du parenchyme pulmonaire sain [19]. L'é tude du coeur reste encore limité e, mais l'é volution des sé quences ciné (en 2D Steady State Free Precession) est trè s prometteuse [20].…”
Section: Une Irm : Quand ?unclassified